2017
DOI: 10.1080/17450128.2017.1290306
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial health concerns among service-seeking orphans in the slums of Kampala

Abstract: Orphans have many unmet needs. The purpose of the current study is to briefly examine the psychosocial correlates linked to being an orphan among service-seeking youth in the slums of Kampala in order to provide guidance for service provision for youth. The current analysis is based on a cross-sectional survey conducted in 2011 which consisted of a convenience sample of youth living in the slums (ages 14–24) attending a drop-in center, Uganda Youth Development Link (UYDEL). Bivariate and multivariable analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Our study found parental death to be a significant event due to both loss of economic and social support which impacted the drug use trajectories of many WWUDHIV. This is in line with data from other studies that have found orphanhood to be associated with drug use [ 28 ]. A life course perspective complements the life history approach by considering the influence of broader social, cultural, and economic factors that shape adolescent girls and young women’s life trajectories.…”
Section: Discussionsupporting
confidence: 92%
“…Our study found parental death to be a significant event due to both loss of economic and social support which impacted the drug use trajectories of many WWUDHIV. This is in line with data from other studies that have found orphanhood to be associated with drug use [ 28 ]. A life course perspective complements the life history approach by considering the influence of broader social, cultural, and economic factors that shape adolescent girls and young women’s life trajectories.…”
Section: Discussionsupporting
confidence: 92%
“…Among the youth who reported drinking, problem drinking was associated with orphan status in both the separate gender logistic models and the overall logistic model. Alcohol prevention interventions for orphans should be examined for this population, as orphans are also at a heightened risk of experiencing other adverse health outcomes [38].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is a hypothesized bidirectional relationship between depression and the SAVA syndemic components [13][14][15][16][17]. Lastly, orphanhood is strongly associated with alcohol use and substance abuse more broadly [18,19]. Through a lack of parental oversight, orphans may engage in risky sexual behaviors, potentially leading to HIV infection [20,21].…”
Section: Introductionmentioning
confidence: 99%